2021
DOI: 10.1101/2021.03.17.21253408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The tumor burden of metastatic colorectal cancer patients at initial diagnosis, pre- versus post-Covid-19 lockdown

Abstract: Background: The COVID-19 pandemic led to a significant reduction in the provision of screening, case identification and hospital referrals to cancer patients. To our knowledge, no study has yet correlated quantitatively the consequences of these limitations for cancer patient management. This study evaluates the implications of such reductions for patients newly diagnosed with metastatic colorectal cancer (mCRC) in both the pre- and post-lockdown periods. Methods: We examined 80 newly identified mCRC patients… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In combination, these data suggest that there could be a secondary increase in cancer mortality to COVID-19 becoming evident in several years. A French study further showed worse survival rates of patients with metastatic colon cancer diagnosed during the first lockdown, presumably due to a higher tumor burden [8]. On the other hand, two recent database analyses for breast and prostate cancer could not confirm the reduced prognosis for delayed treatment in early-stage cancer [9,10].…”
Section: Dear Editormentioning
confidence: 98%
“…In combination, these data suggest that there could be a secondary increase in cancer mortality to COVID-19 becoming evident in several years. A French study further showed worse survival rates of patients with metastatic colon cancer diagnosed during the first lockdown, presumably due to a higher tumor burden [8]. On the other hand, two recent database analyses for breast and prostate cancer could not confirm the reduced prognosis for delayed treatment in early-stage cancer [9,10].…”
Section: Dear Editormentioning
confidence: 98%